Monitoring vegetation dynamics in East Rennell Island World Heritage Site using multi-sensor and multi-temporal remote sensing data. Issue 3 (3rd March 2020) - Wang, Mengmeng; He, Guojin; Ishwaran, Natarajan; Hong, Tianhua; Bell, Andy; Zhang, Zhaoming; Wang, Guizhou; Wang, Meng
ABSTRACT: East Rennell of Solomon Island is the first natural site under customary law to be inscribed on UNESCO's World Heritage List. Potential threats due to logging, mining and agriculture led to the site being declared a World Heritage in Danger in 2013. For East Rennell World Heritage Site (ERWHS) to 'shed' its 'Danger' status the management must monitor forest cover both within and outside of ERWHS. We used satellite data from multiple sources to track forest cover changes for the entire East Rennell island since 1998. 95% of the island is still covered by undisturbed forests; annual average normalized difference vegetation index (NDVI) for the whole island was above 0.91 in 2015. However, vegetation cover in the island has been slowly decreasing, at a rate of –0.0011 NDVI per year between 2000 and 2015. This decrease less pronounced inside ERWHS compared to areas outside. While potential threats due to forest clearing outside ERWHS remain the forest cover change from 2000 to 2015 has been below 15%. We suggest ways in which the Government of Solomon Islands could use our data as well as unmanned air vehicles and field surveys to monitor forest cover change and ensure the future conservation of ERWHS.